Eye Movement Desensitization and Reprocessing (EMDR) therapy as a treatment for depression - Su, Yile (Kansas State University, 2018)
This study examined the efficacy of EMDR therapy as a treatment for unipolar depression. Results provide preliminary evidence for the efficacy of EMDR therapy. Of the 12 participants that received 10 sessions of EMDR therapy, four met the criteria for “Recovered,” six “Improved” and two reported no change in severity of depressive symptoms. Results further indicated that participants who experienced decline in depressive symptoms within the first six sessions of treatment had a higher probability to be meet the criteria for “Recovered.” A small sample comparison between EMDR therapy (n = 4) and CBT (n = 4) did not find any significant difference in terms of treatment outcome. In phase 2, participants in both groups either improved or recovered after 10 sessions of treatment. Sudden gains analysis indicated that 5 out of 12 EMDR therapy participants had sudden gains. Participants in sudden gains group were more likely to meet “Recovered” criteria than participants in no-gains group. Examination of attention bias found that depression was positively related to negative affect fixation duration and negatively related to positive affect fixation duration when only using female affect images. These findings support previous research that used attention bias to differentiate depressed and non-depressed persons. Clinical implication and further research are discussed.
Keywords: Treatment; EMDR therapy; Sudden gains; Attention biasDepression